Market survey for the marketing of cape gooseberry Physalis peruviana L. in Nariño - Coral T, Lilian Graciela; Torres Martinez, Francisco; Yepez Chamorro, Bayardo (Revista de Ciencias Agrícolas, 2012)
This study in the municipality of Puerres is a contribution to knowledge of the current market situation of Cape gooseberry, since labor is the backbone of much of the population of the municipality and especially of the Association of Small Farmers of Puerres ASOPEP. Marketing channels was analyzed, product characteristics at the time of leaving the farm and the Association as a productive institution. The offer represented by the farm production is 39.060 kg.year which are distributed in 4,2 hectares and the unmet demand is estimated at 28.392 kg.year. The high production costs, low yield per hectare of fruit and low sales prices do not allow producers to profit, therefore, is necessary to evaluate and rethink this productive activity. With respect to margins, market intermediaries and supermarkets places have higher trading profits while producer participation is minimal.